2021
DOI: 10.1002/jbm.b.34835
|View full text |Cite
|
Sign up to set email alerts
|

Surface modifications to enhance osseointegration–Resulting material properties and biological responses

Abstract: As life expectancy and the age of the general population increases so does the need for improved implants. A major contributor to the failure of implants is poor osseointegration, which is typically described as the direct connection between bone and implant. This leads to unnecessary complications and an increased burden on the patient population. Modification of the implant surfaces through novel techniques, such as varying topography and/or applying coatings, has become a popular method to enhance the osseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 150 publications
(235 reference statements)
0
29
0
Order By: Relevance
“…Several studies reported that hydrophilicity and surface roughness are critical parameters in the implant-tissue interaction and osseointegration. In particular, hydrophilic surfaces are more desirable than hydrophobic ones in view of their interactions with biological fluids, cells, and tissues [11][12][13]. The modification of the implant surface topography at nanoscale level has been largely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that hydrophilicity and surface roughness are critical parameters in the implant-tissue interaction and osseointegration. In particular, hydrophilic surfaces are more desirable than hydrophobic ones in view of their interactions with biological fluids, cells, and tissues [11][12][13]. The modification of the implant surface topography at nanoscale level has been largely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that surface modifications allow harnessing of the biological response that may significantly reduce implant failure or patient rejection. Although appropriate biological responses being triggered by certain surface modifications are known, there is still a long way to go in developing biomaterials with the optimal surface features that ensure a successful osseointegration process [ 80 ]. Many techniques have been described for obtaining positive surface modifications.…”
Section: Discussionmentioning
confidence: 99%
“…By fabricating the nanostructured surface, the surface nano-topological pattern is formed simultaneously. 13 Studies show that nano-topography can improve osseointegration in several aspects, including protein adsorption, 14 , 15 fibrin clot attachment, 16 , 17 cell behavior 18 , 19 and immune response. 20 On one side, the nano-topological oxide layer increases cell adhesion and influences the secretion of cytokines.…”
Section: Introductionmentioning
confidence: 99%